Effect of Modified Pin Profile and Process Parameters on the Friction Stir Welding of Aluminum Alloy 6061-T6 - J. C. Verduzco Juárez; G. M. Dominguez Almaraz; R. García Hernández; J. J. Villalón López (Advances in Materials Science and Engineering)
This work deals with the effect of a new “bolt-head” pin profile on the friction stir welding performance of the aluminum alloy 6061-T6, compared to traditional pin profiles. Friction stir welding parameters such as the tool rotation speed and the welding speed were investigated together with the different pin profiles; the results show that the new “bolt-head” pin profile leads to better mechanical properties of welded specimens. The pin profiles used in this work were the straight square (SS), straight hexagon (SH), taper cylindrical (TC), and the straight hexagon “bolt-head” (SHBH). It was found that the last pin profile improves the material flow behavior and the uniform distribution of plastic deformation and reduces the formation of macroscopic defects on the welded zone. Mechanical tensile tests on welded specimens were performed to determine the tensile strength: the specimens welded with the SHBH pin profile have shown the highest mechanical properties. An approach is presented for material flow on this aluminum alloy using the SHBH pin profile, which is related to the improvement on the resulting mechanical properties.